Hereditary Persistence Of Alpha-fetoprotein: A Rare Entity From A Primary Care Center In Bangladesh - Podder, Chinmay Saha; Amin, Mohammod Feroz; Chowdhury, Nandini (Bangladesh Journal of Medicine, 2023)
Hereditary persistence of alpha- fetoprotein (HFAFP) is a rare benign autosomal dominant disorder.Here we report a case of 15 years old boy who was found to have elevated alpha-fetoprotein during her routine evaluation for gynaecomastia. All other common possibilities for raised alpha-fetoprotein were excluded.Subsequently, 2 of his family members were found to have raised alpha-fetoprotein.One is his father and another one is his brother.Raised alpha-fetoprotein has a wide differential diagnosis including, pregnancy, germ cell tumors, hepatocellular carcinoma and others.But after exclusion of other possibilities, persisting elevated alphafetoprotein raises the suspicion for HPAFP.Testing other family members for AFP and specific genetic study aid in diagnosis. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 216-217